Modeling cosmic ray neutron field measurements. Issue 8 (25th August 2016) - Andreasen, Mie; Jensen, Karsten H.; Zreda, Marek; Desilets, Darin; Bogena, Heye; Looms, Majken C.
Abstract: The cosmic ray neutron method was developed for intermediate‐scale soil moisture detection, but may potentially be used for other hydrological applications. The neutron signal of different hydrogen pools is poorly understood and separating them is difficult based on neutron measurements alone. Including neutron transport modeling may accommodate this shortcoming. However, measured and modeled neutrons are not directly comparable. Neither the scale nor energy ranges are equivalent, and the exact neutron energy sensitivity of the detectors is unknown. Here a methodology to enable comparability of the measured and modeled neutrons is presented. The usual cosmic ray soil moisture detector measures moderated neutrons by means of a proportional counter surrounded by plastic, making it sensitive to epithermal neutrons. However, that configuration allows for some thermal neutrons to be measured. The thermal contribution can be removed by surrounding the plastic with a layer of cadmium, which absorbs neutrons with energies below 0.5 eV. Likewise, cadmium shielding of a bare detector allows for estimating the epithermal contribution. First, the cadmium difference method is used to determine the fraction of thermal and epithermal neutrons measured by the bare and plastic‐shielded detectors, respectively. The cadmium difference method results in linear correction models for measurements by the two detectors, and has the greatest impact on the neutron intensity measured by the moderated detector at the ground surface. Next, conversion factors are obtained relating measured and modeled neutron intensities. Finally, the methodology is tested by modeling the neutron profiles at an agricultural field site and satisfactory agreement to measurements is found. Key Points: Additional applications of the cosmic ray neutron method can be explored using neutron modeling A method to align and make measured and modeled neutron intensities comparable is proposed The methodology is validated by modeling measured thermal and fast neutron profiles